The Value of Dayak Gawai Tradition: Learning Kantu’ Dayak Literature - Restoeningroem Restoeningroem; Aster Pujaning Ati; Sigit Widiyarto; Nana Suyana (STAI Hubbulwathan Duri, 2023)
Literature learning in schools is still inadequate. This is caused by the content of literature only as a complement to Indonesian language subjects and several other obstacles, such as learning methods in the classroom that are not yet optimal. The purpose of this study is firstly to find out what values are contained in the Gawai Dayak tradition of the Kantu tribe' and secondly to make the Gawai Dayak tradition a literary subject for high school students. This study uses a qualitative method with an ethnographic approach. Respondents in this study were 1 village head, 2 cultural observers, 1 head of an art studio, and 6 Kantu' Dayak people. Data collection methods include observation, interviews, and documentation. The collected data is selected, then presented and verified and conclusions are drawn. The validity of the data used triangulation method. There are cultural values, religious/religious values, and solidarity values. The revitalization of traditions is carried out by making textbooks containing the Gawai Dayak tradition and mantras as local literature that needs to be preserved.